Las NIIF para pymes sección 3- presentación de estados financieros en las empresas constructoras de la ciudad de Cuenca Ecuador en el periodo 2019-2020 - Diana Cristina, Bojorque Velastegui (2022)
ABSTRACT: This research work has been framed in applying the IFRS for SMEs, section 3 - Presentation of financial statements in construction companies of the city of Cuenca Ecuador in the period 2019-2020. Provide accounting with a legal, persistent, and timely basis. Each entity requires a timely, transparent, and effective accounting scheme applied daily in its accounting transactions to obtain financial statements that reflect the economic reality. This study required field research through surveys of accountants from each of the 201 construction SMEs, which identified the direct causes of insufficient control and accounting ignorance of IFRS. (International Financial Reporting Standards) for SMEs. He concludes that they represent the purpose of using a global language in accounting terms. Therefore, it is recommended to establish a benchmark and adequately guide the valuation of financial transactions. Keywords: Accounting, IFRS, SMEs, Financial Statements.